A study on Shojinka design for automobile engine piston-rod manufacturing. (January 2021) - Wang, Peng-Sen; Lin, Chih-Ching; Yang, Taho
Highlights: Shojinka is the flexibility in the number of workers to adapt to demand changes. Shojinka is often combined with cellular layout design configuration. An engine piston-rod manufacturing process is adopted for empirical illustration. An improvement of 49.7% for worker productivity is realized. The expected improvement for the future design is 128.5% for worker productivity. Abstract: Adapting the number of workers in a workshop in response to changes in the customer demand is termed Shojinka, and is often combined with a cellular layout design configuration. In contrast to fixed staffing level designs, Shojinka achieves a notably improved productivity in changeable environments. Based on the continuous flow design guidelines presented in the literature, this study proposes a four-step procedure for evaluating and generating three stage-wise designs (namely existing, improved and future) in pursuit of Shojinka objectives. The four-step procedure commences by analyzing the layout and performance of the existing process (Step 1). An improved layout design is then established using the continuous flow guidelines (Step 2). The standard operations which achieve a balanced production with the minimal labor requirement are then determined (Step 3). Finally, the Chaku-Chaku principle is applied to determine the ideal layout which minimizes the labor requirement and maximizes the productivity (Step 4). The feasibility of the proposed approach is demonstrated using a real-world automobile engine piston-rod manufacturing process for illustration purposes. It is shown that the improved and future designs improve the average worker productivity by 49.7% and 128.5%, respectively, compared to the existing design. Thus, both the effectiveness of the proposed methodology and the contribution of the present study are justified.